The banishment of Beverland: sex, scripture, and scholarship in the seventeenth-century Dutch Republic - Hollewand, K (2016)
Hadriaan Beverland (1650-1716) was banished from Holland in 1679. Why did this humanist scholar get into so much trouble in the most tolerant part of Europe in the seventeenth century? In an attempt to answer this question, this thesis places Beverland’s writings on sex, sin, Scripture, and scholarship in their historical context for the first time. Beverland argued that lust was the original sin and highlighted the importance of sex in human nature, ancient history, and his own society. His works were characterized by his erudite Latin, satirical style, and disregard for traditional genres and hierarchies in early modern scholarship. Dutch theologians disliked his theology and exegesis, and hated his use of erudition to mock their learning, morality, and authority. Beverland's humanist colleagues did not support his studies either, because they believed that drawing attention to the sexual side of the classics threatened the basis of the humanist enterprise. When theologians asked for his arrest and humanist professors left him to his fate, Dutch magistrates were happy to convict Beverland because he had insolently accused the political and economic, as well as the religious and intellectual elite of the Dutch Republic, of hypocrisy. By restricting sex to marriage, in compliance with Reformed doctrine, secular authorities upheld a sexual morality that was unattainable, Beverland argued. He proposed honest discussion of the problem of sex and suggested that greater sexual liberty for the male elite might be the solution. Beverland’s crime was to expose the gap between principle and practice in sexual relations in Dutch society, highlighting the hypocrisy of a deeply conflicted elite at a precarious time. His intervention came at the moment when the uneasy balance struck between Reformed orthodoxy, humanist scholarship, economic prosperity, and patrician politics, which had characterized the Golden Age of the Dutch Republic, was disintegrating, with unsettling consequences for all concerned. Placing Beverland's fate in this context of change provides a fresh perspective on the intellectual environment of the Republic in the last decades of the seventeenth century.